Jejunal perforation due to single ascaris lumbricoides – a case report. - Reetinder C; Pankaj KG; Divya S; Ashwani K; Vijay KS; Amit S (Department of Surgery, UKM Medical Centre, 2013)
Ascriasis is a common infection in underdeveloped and developing countries and usually detected incidentally on evaluation of nonspecific pain abdomen. Complications related to ascariasis occur mainly due to heavy worm load. We here report a rare case, in which a single live ascaris worm had caused jejunal perforation.